Getting There? Together. Cultural Framing of Augmented and Virtual Reality for Art Education - Back, Regina Maria; Wenrich, Rainer; Dorner, Birgit (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Informal learning contexts of creating and exploring artefacts through Augmented Reality (AR) and Virtual Reality (VR) are increasingly common. Nevertheless, insights on art educators' perspectives on potential for conceptualization and classroom implementation are scarce. In this study, twenty art educators with diverse backgrounds (elementary and secondary school, special education) were exploring a selection of AR/VR applications during online workshops. In addition, six media artists working on AR/VR were sharing experiences in educational contexts. Both art educators as well was artists are pointing out ways of integrating a variety of AR/VR applications in art education teaching practise, from creating in multiplayer mode to exploring artefacts and loci in SocialVR. Grounded Theory Methodology, specifically Situational Analysis as well as Visual Grounded Theory Methodology was applied. Core insights are differing media cultural perspectives in proximity and distance to AR/VR related "worlds", resulting in different journeys from first encounter to conceptualization and implementation in educational practice.